Au@Ag SERRS tags coupled to a lateral flow immunoassay for the sensitive detection of pneumolysin. Issue 5 (23rd January 2017) - Blanco-Covián, Lucía; Montes-García, Verónica; Girard, Alexandre; Fernández-Abedul, M. Teresa; Pérez-Juste, Jorge; Pastoriza-Santos, Isabel; Faulds, Karen; Graham, Duncan; Blanco-López, M. Carmen
Abstract : SERRS based lateral flow immunoassay for pneumonia biomarker (pneumolysin). Abstract : Establishing a definitive diagnosis of pneumonia using conventional tests is difficult and expensive. Lateral flow immunoassays (LFIAs) are an advantageous point of care (POC) test option, but they have some limitations in terms of detection and quantification. In this work we have developed a lateral flow immunoassay for the ultrasensitive detection of penumolysin employing plasmonic Surface-Enhanced Resonance Raman Scattering (SERRS) tag as labelled probe. The combination of Au@Ag core–shell nanoparticles as plasmonic platform and Rhodamine B Isothiocyanate as Raman reporter has allowed us to fabricate a SERRS tag with high efficiency and reliability. The limit of detection of the SERRS-based LFIA was 1 pg mL −1 . This could be a strong foundation for a pneumonia diagnosis test based on pneumolysin detection.